2020
DOI: 10.3389/fgene.2020.00681
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing of Four Representatives From the Admixed Population of the United Arab Emirates

Abstract: Whole genome sequences (WGS) of four nationals of the United Arab Emirates (UAE) at an average coverage of 33X have been completed and described. The selection of suitable subpopulation representatives was informed by a preceding comprehensive population structure analysis. Representatives were chosen based on their central location within the subpopulation on a principal component analysis (PCA) and the degree to which they were admixed. Novel genomic variations among the different subgroups of the UAE popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The first whole genomes analysis of two UAE nationals 42 , 43 has provided insights into the genomic structure and the putative genetic origins of its population. Following that, a comprehensive, large-scale stratification study of the UAE population concluded that genetic admixture throughout the Arabian Peninsula's eastern shore and south-eastern tip happened gradually and without clear social stratification boundaries 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The first whole genomes analysis of two UAE nationals 42 , 43 has provided insights into the genomic structure and the putative genetic origins of its population. Following that, a comprehensive, large-scale stratification study of the UAE population concluded that genetic admixture throughout the Arabian Peninsula's eastern shore and south-eastern tip happened gradually and without clear social stratification boundaries 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Its pivotal geographic position allowed an influx of Arab tribes and foreign expats from the region, providing a representation of the middle eastern population (31). Admixture analysis has shown consistent patterns of the ethnicities and populations of different parts of the Middle East, demonstrating that the contemporary populations of the UAE is suitable to conduct representative epidemiological studies of the Arab population (31,32).…”
Section: Samplementioning
confidence: 99%
“…Metabolic quantitative trait loci identification analysis revealed genetic loci associated with pharmacological/drug targets on the consanguineous Arab population, which is important to precision P r e p r i n t medicine in the Arab world [30]. Constructing specific references sequences for a subpopulation of Arab ancestry is also important in precision medicine, the initiation of the UAE reference panel is a good initiative [22,31,32].…”
Section: Clinically Relevant Traits and Precision Medicinementioning
confidence: 99%